Online Teaching in Public Campuses during COVID 19: Teachers’ Perceptions - Panthee, Dinesh (Education and Development, 2020)
The coronavirus pandemic has had a profound impact on education. Higher education institutions including public campuses have followed the recourse of online learning as an alternate to the face-to-face learning to minimize this impact and keep the students engaged during the pandemic. This paper discusses the changing scenario of delivering education in higher educational institutions in Nepal. The purpose of this study was to explore teachers’ perceptions on online teaching. It also tried to identify the challenges and opportunities of online teaching in public campuses of Nepal. The study adopted a qualitative research design. Three faculty members of three different campuses from Rupandehi were taken as research participants purposively. The main finding was that the faculty members are ready to adopt online teaching to mitigate the learning loss of the students due to COVID 19. But there are some challenges for conducting online classes like unwillingness of campuses to implement the online classes, lack of physical infrastructures, lack of clear policy, and limited motivating factors for faculty members and students.